Rancang Bangun Sistem Pervasive Pada Rumah Cerdas Berbasis Protokol Message Queue Telemetry Transport dan Webservice - Arnandha Hadi Pranata; Sabriansyah Rizqika Akbar; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Smarthome is a system at the building or house who give a comfortable, safety, secure, and energy savings. The main problem of smarthome occurs about the identification system work in manually. So, it need some smarthome system that pervasively recognizes smarthome devices. Then the owner of smarthome isn't input the information of equipment in manually. This research implementing method of publish subscribe as data communication protocol between smarthome device with smarthome owner and supported by webservice technology to facilitate smarthome owner in monitoring and controlling smarthome furnishings by using owner's smartphone. In publish subscribe method, researcher use MQTT protocol which publisher as message sender that is smarthome furnishings, MQTT broker as server and data communication, and subscriber as recipient of message. From the testing results that have been done 5x to delay is taken on average as follows: publisher - broker = 3.6 ms, broker - subscriber = 195 ms, subscriber - webservice = 1004.7 ms. From these results it can be concluded that the system has successfully identify pervasive devices and that systems work efficiently. The process of sending data occurs very quickly and delay results obtained in a miliseconds.